A Rhetorical-Legal Hermeneutic: Representations of Women in the Qur'an through Balaghah and Their Implications for Islamic Law - Yasmar, Renti; Nurmala, Mia; Nurbayan, Yayan; Erlina, Erlina; Atikah, Tiara (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
This study addresses contested interpretations of women's status in Islamic law by innovatively applying Balaghah (Quranic rhetoric) to analyze gender representations in the Quran. Using rhetorical analysis of kalam khabari (declaratives), kalam insha'i (directives), and kinayah (metaphors), we systematically examine verses concerning inheritance, testimony, and women's rights. Our findings reveal that the Quran's linguistic structures consistently affirm gender equality, contradicting patriarchal readings - particularly through its deliberate use of rhetorical devices in key verses (e.g., Q 4:7, Q 2:282). The study's novelty lies in developing a Balaghah-based framework for Islamic feminist jurisprudence, demonstrating how Quranic rhetoric inherently safeguards women's dignity. This provides: (1) a new methodology for gender-sensitive Quranic exegesis, and (2) textual evidence for reforming patriarchal legal interpretations. These findings are significant for contemporary Muslim societies, offering a Quran-grounded approach to aligning Islamic law with gender justice principles.